2011
DOI: 10.1590/s1807-76922011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge transfer in product development: an analysis of Brazilian subsidiaries of multinational corporations

Abstract: Several studies about knowledge transfer in multinational corporations have found that the process is influenced by factors such as absorptive capacity, tacit knowledge and power relations, all of which impact knowledge sharing strategies between corporate headquarters and foreign subsidiaries. A multiple case study of Brazilian subsidiaries of three multinational corporations using in-depth interviews, based on a conceptual model consisting of four propositions, was conducted to identify factors linked to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
2
5
0
3
Order By: Relevance
“…These results are in line with Schreiber et al (2011), who contended that the crucial element in knowledge transfer process is not the carrier of the original knowledge, but the receiver's perception of the effectiveness and applicability of this transmitted knowledge in its operations. Further data analysis based on Peng (2011) andChang et al (2012) indicated that the ability, motivation and opportunity of manager competencies will maximize the knowledge received by the employees, which in turn will enhance organizational performance.…”
Section: Discussion Implications and Limitationssupporting
confidence: 88%
See 1 more Smart Citation
“…These results are in line with Schreiber et al (2011), who contended that the crucial element in knowledge transfer process is not the carrier of the original knowledge, but the receiver's perception of the effectiveness and applicability of this transmitted knowledge in its operations. Further data analysis based on Peng (2011) andChang et al (2012) indicated that the ability, motivation and opportunity of manager competencies will maximize the knowledge received by the employees, which in turn will enhance organizational performance.…”
Section: Discussion Implications and Limitationssupporting
confidence: 88%
“…Moreover, source managers' knowledge transfer capacity is the ability to articulate uses of their own knowledge, assess the needs and capabilities of the potential recipient and transmit knowledge so that it can be put to use within the recipient organization (Martin and Salomon, 2003). However, Schreiber et al (2011) argued that the crucial element in knowledge transfer is not the carrier of the original knowledge but the receiver's perception of the effectiveness and applicability of this transmitted knowledge in its operations. Thus, Wang and Wang (2012) confirmed that the process of knowledge transfer is based not only on the cognitive characteristics of the user that is the focus of the interpretation but also on the method by which it is presented to the user and represented by the codification used to distinguish that specific knowledge.…”
Section: Mediating Role Of Knowledge Received By Employeesmentioning
confidence: 99%
“…Cria--se, assim, maior vantagem competitiva para a empresa. Isso só acontece, no entanto, se a subsidiária possui certa autonomia e tem capacidade para difundir esse conhecimento internamente (SCHREIBER et al, 2011). Boehe (2007) afirma que a autonomia de uma subsidiária está diretamente ligada à existência, ou não, de hierarquia organizacional entre a filial e sua matriz.…”
Section: Geração E Difusão De Conhecimento Da Subsidiáriaunclassified
“…No entanto, fatores específicos da subsidiária brasileira, como o ritmo intenso de trabalho, busca constante por novos insumos, processos e tecnologias, e experiência e expertise no mercado calçadista, criam um ambiente onde novos conhecimentos são desenvolvidos em todas as coleções. Esses elementos desenvolvem a capacidade tecnológica da subsidiária brasileira e sua cpacidade de geração de conhecimento, segundo Schreiber et al (2011).…”
Section: A Geração De Conhecimento Pela Subsidiáriaunclassified
“…The knowledge transfer between subsidiaries have found that the process is in°uenced by factors such as subsidiaries' capacity, tacit knowledge and power relations, all of which impact knowledge transfer strategies between corporate headquarters and subsidiaries (Schreiber et al, 2011). Subsidiary knowledge, at least potentially transferable, may also be built from internal through interaction with other subsidiaries where the process of building knowledge re°ect with knowledge elements in other parts of the MNCs (Foss and Pedersen, 2002).…”
Section: Knowledge Transfer Between Subsidiariesmentioning
confidence: 99%